Conjugal Transfer of the Pathogenicity Island ROD21 in Salmonella enterica serovar Enteritidis Depends on Environmental Conditions - Salazar-Echegarai, Francisco J. (Public Library of Science, 2014)
Unstable pathogenicity islands are chromosomal elements that can be transferred from one bacterium to another. Salmonella enterica serovar Enteritidis (S. Enteritidis) is a pathogenic bacterium containing such unstable pathogenicity islands. One of them, denominated ROD21, is 26.5 kb in size and capable of excising from the chromosome in certain culture conditions, as well as during bacterial infection of phagocytic cells. In this study we have evaluated whether ROD21 can be effectively transferred from one bacterium to another. We generated a donor and several recipient strains of S. Enteritidis to carry out transfer assays in liquid LB medium. These assays showed that ROD21 is effectively transferred from donor to recipient strains of S. Enteritidis and S. Typhimurium. When Escherichia coli was used as the recipient strain, ROD21 transfer failed to be observed. Subsequently, we showed that a conjugative process was required for the transfer of the island and that changes in temperature and pH increased the transfer frequency between Salmonella strains. Our data indicate that ROD21 is an unstable pathogenicity island that can be transferred by conjugation in a species-specific manner between Salmonellae. Further, ROD21 transfer frequency increases in response to environmental changes, such as pH and temperature.